Odpowiedź :
Mnozenie to wielokrotne dodawanie
2⁵ + 2⁵ = 2⁶
2*2⁵=2₆
(-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ + (-3)³ + (-3)³=3*(-3)³ ale (-3)³=-(3)³
3*(-3)³ =-3*3³=-3⁴
Pozdr
Hans
2⁵ + 2⁵ = 2⁶
2*2⁵=2₆
(-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ + (-3)³ + (-3)³=3*(-3)³ ale (-3)³=-(3)³
3*(-3)³ =-3*3³=-3⁴
Pozdr
Hans
a) 2⁵ + 2⁵ = 2⁶
2⁵ = 32
2⁶ = 64
2⁵ + 2⁵ = 2⁶
32 + 32 = 64
b) (-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ = -27
-3⁴ = -81
(-3)³ + (-3)³ + (-3)³ = -3⁴
(-27) + (-27) + (-27) = -81
2⁵ = 32
2⁶ = 64
2⁵ + 2⁵ = 2⁶
32 + 32 = 64
b) (-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ = -27
-3⁴ = -81
(-3)³ + (-3)³ + (-3)³ = -3⁴
(-27) + (-27) + (-27) = -81
2⁵ + 2⁵ = 2*2⁵ = 2¹*2⁵=2⁶
(-3)³ + (-3)³ + (-3)³ = 3*(-3)³=3¹*(-3)³=-3⁴
(-3)³ + (-3)³ + (-3)³ = 3*(-3)³=3¹*(-3)³=-3⁴